2009
DOI: 10.1038/eye.2009.76
|View full text |Cite
|
Sign up to set email alerts
|

Correlation in foveal thickness measurements between spectral-domain and time-domain optical coherence tomography in normal individuals

Abstract: Purpose To compare a time-domain (Stratus) and a spectral-domain (Spectralis)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
4
23
2
Order By: Relevance
“…10,11 With an observed correlation coefficient of 0.98 in our study, our results are consistent with the previous reports.…”
Section: Eyes With Dmesupporting
confidence: 83%
“…10,11 With an observed correlation coefficient of 0.98 in our study, our results are consistent with the previous reports.…”
Section: Eyes With Dmesupporting
confidence: 83%
“…Similar to the index patient, the affected brother (II-5, Figure 1B), was heterozygous for both mutations while the unaffected brother (II-1, Figure 1B) carried only the nonsense mutation. (Carpineto et al 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Spectralis HRA þ OCT incorporated a new algorithm of RNFL analysis of the optic nerve head (Figure 1b). [8][9][10][11] As the new technology becomes more ubiquitous, patients with previous TD OCT imaging will likely undergo SD OCT imaging in the future. Therefore, correlation and agreement between the two technologies become clinically relevant to detect change in RNFL thickness in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…SD OCT acquires A-scans B100 times faster than TD OCT, which improves motion artefacts. [8][9][10][11] A commercially available third-generation TD OCT (Stratus OCT; software version 4.0.1, Carl Zeiss Meditec, Dublin, CA, USA) provides image resolution of 8-10 mm (Stratus RNFL analysis printout is depicted in Figure 1a). Previous studies have demonstrated its good reproducibility of retinal measurements and high specificity and sensitivity for detection of glaucomatous damage.…”
Section: Introductionmentioning
confidence: 99%